2017
DOI: 10.1007/s00127-017-1342-8
|View full text |Cite
|
Sign up to set email alerts
|

Military service and crime: new evidence

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
(14 reference statements)
2
8
0
Order By: Relevance
“…The substance use mechanisms accounted for a substantial proportion (approximately 70%) of the mediating effect. As such, these results support the study hypotheses and previous research regarding the salience of alcohol and drug use difficulties that occur in this population (Snowden et al, 2017). Furthermore, moral injury also provided an important mediating effect, suggesting that additional research on this construct as well as clinical attention could be fruitful.…”
Section: Discussionsupporting
confidence: 90%
“…The substance use mechanisms accounted for a substantial proportion (approximately 70%) of the mediating effect. As such, these results support the study hypotheses and previous research regarding the salience of alcohol and drug use difficulties that occur in this population (Snowden et al, 2017). Furthermore, moral injury also provided an important mediating effect, suggesting that additional research on this construct as well as clinical attention could be fruitful.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the study findings may be considered generalizable given the rigorous design of the NESARC-III and the comparability to previous studies, for example, 10.6% prevalence of incarceration in this study was similar to 11.8% found in another study (Greenberg & Rosenheck, 2014). We could find no previous epidemiological study of lifetime incarceration among veterans, but our 15% prevalence rate was expectedly lower than a previous study that broadly examined any criminal justice involvement among veterans reporting a rate of 31.1% (Snowden et al, 2017).…”
Section: Study Limitationssupporting
confidence: 78%
“…Nationally representative surveys in the US found that almost one-third of veteran respondents (31.1%) had ever been arrested and booked, a rate significantly higher than among civilians (18.0%). 7 Another study found that although military service during wartime was inversely related to subsequent incarceration, veterans of the post-1973 All Volunteer Force were more likely to be incarcerated than civilians and veterans who served during the draft era. 1 Among veterans in treatment for substance use or mental health problems, a history of criminal justice involvement is the norm rather than the exception.…”
Section: Introductionmentioning
confidence: 99%